2018
DOI: 10.1136/sextrans-2017-053229
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the well-being of patients diagnosed with Chlamydia trachomatis: a cross-sectional study

Abstract: Women and men reacted differently when diagnosed with CT. Women worried more about complications and more often blamed themselves for being infected. Being aware of these gender differences may be important when planning preventive measures and during counselling of CT-infected patients. Persons working with patients with CT must also be aware of the high frequency of harmful alcohol consumption among their patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
1
4
0
2
Order By: Relevance
“…One RCT reported on adverse antibiotic events, 5 and 10 uncontrolled cohort studies reported on psychosocial harms. 20,[36][37][38][39][40][41][42][43][44] No studies examined harms of screening for gonorrhea.…”
Section: Recommendationmentioning
confidence: 99%
See 1 more Smart Citation
“…One RCT reported on adverse antibiotic events, 5 and 10 uncontrolled cohort studies reported on psychosocial harms. 20,[36][37][38][39][40][41][42][43][44] No studies examined harms of screening for gonorrhea.…”
Section: Recommendationmentioning
confidence: 99%
“…One RCT (n = 37 543 tested; n = 4574 patients who received a diagnosis of chlamydia; number treated not reported) reported no adverse events from antibiotic treatment for chlamydia (very lowcertainty evidence). 5 Cohort studies 20,[36][37][38][39][40][41][42][43][44] reported on a vari ety of psychosocial harms of screening that were synthesized narratively; low or very lowcertainty evidence indicated that undergoing screening may lead to feelings of stigmatization (e.g., guilt, embarrassment, social disapproval) or anxiety about future infertility, sexuality or risk of infection in a small to moderate proportion of individuals (50-400 per 1000 individuals screened). The number of individuals affected in the entire eligible screen ing population is likely smaller.…”
Section: Harms Of Screeningmentioning
confidence: 99%
“…Onze études sur les préjudices associés au dépistage de la chlamydia ont été recensées. Un ERC a fait état des effets indésirables des antibiotiques 5 et 10 études de cohortes non contrôlées ont fait état de préjudices psychosociaux 20,[36][37][38][39][40][41][42][43][44] . Aucune étude ne s'est penchée sur les préjudices associés au dépistage de la gonorrhée.…”
Section: Encadré 1 : Sommaire De La Recommandation Pour Les Médecins Les Responsables Des Orientations Politiques Et Les Patientsunclassified
“…Un ERC (n = 37 543 personnes testées; n = 4574 patients ayant reçu un diagnostic de chlamydia; nombre de personnes traités non précisé) n'a fait état d'aucun effet indésirable de l'antibiothérapie pour la chlamydia (données de très faible certitude) 5 . Des études de cohorte 20,[36][37][38][39][40][41][42][43][44] ont fait état de divers préjudices psychosociaux associés au dépistage; ils ont été synthétisés de façon narrative. Des données de faible ou très faible certitude ont indiqué que le dépistage pouvait susciter des sentiments de stigmatisation (p.…”
Section: Préjudices Associés Au Dépistageunclassified
“…In addition to these, Brook’s editorial12 considers the challenges to developing countries seeking to meet UNAIDS 90:90:90 targets by poor access to viral-load testing, and the potential for these to be addressed by point-of-care (POCT) viral-load testing, if this ever becomes available at reasonable cost and the technology proves serviceable in these contexts. Other studies explores the relative psychological impact on men and women of diagnosis with chlamydia13; the development of azithromycin resistance in relation to earlier treatment with the drug for STIs14; the social determinants of condomless anal intercourse in Swedish MSM15 and the prevalence of HPV in China by region, sexual orientation and HIV status 16…”
mentioning
confidence: 99%